Preserving Autonomy: - Barney G. Glaser (Grounded Theory Review: An International Journal)
The most desirable cry for help is a specific question requiring only a direct specific answer. However, this seldom occurs in over half the cries for help. Most requests are not that simple nor answers that brief. In this chapter we see the amazing variations in request and replies for help. The novice proceeds as best as possible to the highly valued goal—the PhD.